Assessment of Atrial Electromechanical Delay and Left Atrial Mechanical Functions in Patients with Ulcerative Colitis. Issue 7 (23rd March 2016) - Nar, Gokay; Ergul, Bilal; Aksan, Gokhan; Inci, Sinan
Abstract : Objective: Ulcerative colitis (UC) is a common inflammatory bowel disease causing systemic inflammation, which may also affect the cardiovascular system, as well as other organ systems. The aim of the current study was to evaluate left atrial (LA) mechanical functions and duration of atrial electromechanical delay (AEMD) with echocardiography in patients with UC. Method: A total of 91 patients, 45 with UC (Group 1) and 46 healthy individuals as control (Group 2) were included in the study. The demographic and laboratory data were recorded, and echocardiographic measurements were taken for all patients. Results: In the evaluation of basal clinical and laboratory findings, no difference was detected between the two groups, except for white blood cell count (WBC) (8.26 ± 2.71 vs. 7.06 ± 1.70, P = 0.013) and high‐sensitivity C‐reactive protein (Hs‐CRP; 3.4 ± 1.7 vs. 1.0 ± 0.8, P < 0.001). The echocardiographic assessment revealed that the diastolic parameters such as E‐, E/A‐, and E‐ waves decreased in the UC group when compared to the control group. LA mechanical functions were different between groups, except for left atrial (LA) maximal volume: LA minimum volume (22.2 ± 12.9 vs. 15.3 ± 4.7, P = 0.001), LA volume before atrial systole (29.9 ± 14.2 vs. 24.2 ± 4.9, P = 0.021), LA ejection fraction (27.4 ± 16.5 vs. 38.6 ± 10.1, P < 0.001), LA total emptying volume (17.9 ± 6.9 vs. 21.9 ± 5.9, P = 0.004), LA active emptying fraction (27.4 ± 16.5 vs. 38.6 ± 10.1, P < 0.001), LA active emptying volume (7.7 ± 3.6 vs. 9.4 ± 2.9, P = 0.013), LA passive emptying fraction (26.8 ± 10.2 vs. 33.2 ± 9.2, P = 0.002), and LA passive emptying volume (10.3 ± 4.9 vs. 12.5 ± 4.5, P = 0.029). There was a significant difference between the groups in terms of AEMD durations, except time interval from the onset of the P‐wave on the surface ECG to the peak of the late diastolic wave (PA) of the tricuspid valve. The correlation analysis revealed that age and duration of disease were correlated with AEMD. Conclusion: The current study reported that LA volume and mechanical functions degenerated and AEMD increased in patients with UC when compared to the control group. These findings demonstrate that UC may have effects on LA electromechanical functions related to duration of disease.